2010
DOI: 10.1182/blood.v116.21.4840.4840
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bcl-2, Bax and ACE Expression In CD34+ Cells of Peripheral Blood and Bone Marrow In Patients with Acute Leukemia During Induction Therapy

Abstract: 4840 The causes of drug resistance in acute leukemias (AL) have been studied very intensively and the key research was done on Bcl-2 family proteins. Last studies have showed that high level Bcl-2 expression in acute leukemia is really associated with drug resistance andpoor prognosis [Haematologica 2007, U. Testa]. It was demonstrated that lower Bax/Bcl-2 ratio (<0,3) was associated with FAB M0-M1 classes (p=.00001), poor-risk cytogenetics and poor prognosis [Blood 2003, G. Poeta]. But there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…31 ACE and p53 expressions were detected in the CD34+ cells of patients with acute leukemia during and after induction chemotherapy. 17 ACE -expressing macrophages in lymph nodes of patients with Hodgkin’s disease have been detected. 15 Enhanced ACE activity was also linked to multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…31 ACE and p53 expressions were detected in the CD34+ cells of patients with acute leukemia during and after induction chemotherapy. 17 ACE -expressing macrophages in lymph nodes of patients with Hodgkin’s disease have been detected. 15 Enhanced ACE activity was also linked to multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic malignant blood cells are derived from leukaemic stem cells within a complex series of pathological proliferative steps. There is preliminary evidence that the local BM RAS could affect neoplastic tumoral blood cell production [34][35][36][40][41][42][43][44][45]. The prominent functions of the local RAS in primitive embryonic haematopoiesis [21][22][23][24] support further the hypothesis that the local autocrine BM RAS could be active in neoplastic haematopoiesis.…”
Section: Introductionmentioning
confidence: 92%
“…Immunohistochemical studies have shown the possible role of ACE/RAS in BM by evaluating ACE expression in normal BM, several myeloproliferative disorders and myelodysplasia [51]. ACE and p53 expression were detected in CD34 + cells in patients with acute leukaemia during and after the induction of chemotherapy [43]. ACE-expressing macrophages in the lymph nodes of patients Hodgkin's disease have been detected [118].…”
Section: Acementioning
confidence: 99%
“…Malignant blood cells, including multiple myeloma (MM) cells, are derived from the clonal neoplastic stem cells within a complex series of pathological proliferative steps. The local BM RAS could affect neoplastic tumoral blood cell production [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The local RAS is effective even in embryonic hematopoiesis [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%